Severe local convective storms in Bangladesh: Part I. Climatology - Yamane, Y.; Hayashi, T.; Dewan, Ashraf; Akter, F. (Elsevier, 2010)
This paper presents the climatology of severe local convective storms in Bangladesh. We collected sufficient severe local convective storm events over a long period (2,324 events from 1990 to 2005) to compile reliable climatological statistics by surveying the literature. Severe local convective storms frequently occur during the pre-monsoon season from March to May, peaking in April. The highest frequency was found to be at 16–17 Local Standard Time (LST) and 20–21 LST, with lower activity around midnight and early morning. It was also found that the occurrence of severe local convective storms is more concentrated in the central region of Bangladesh, and tends to spread northward during the pre-monsoon season.